A high-resolution fMRI approach to characterize functionally distinct neural pathways within dopaminergic midbrain and nucleus accumbens during reward and salience processing - Richter, Anja; Reinhard, Fabian; Krämer, Bernd; Gruber, Oliver (European neuropsychopharmacology, 2020)
Processing of reward and salience without reward association are known to critically rely on the dopamine system. A growing body of evidence from animal studies suggests that both functions may be subserved by distinct subregions in midbrain and ventral striatum, specifically nucleus accumbens (NAcc). Yet in vivo investigation of these brain structures in humans has been rare. Here we examined blood oxygen level dependent signals in response to frequently presented rewarding events and infrequently presented neutral events in 20 healthy subjects using high-resolution functional magnetic resonance imaging (fMRI) for imaging the human midbrain and NAcc. The present findings revealed distinct activation patterns in brain regions of interest, namely increased activation in substantia nigra pars compacta (SNc) and dorsolateral NAcc in response to neutral events, while the VTA and both the ventromedial and dorsolateral NAcc were significantly activated due to rewarding events. Moreover, psychophysiological interaction analyses demonstrated regionally specialized processing pathways, such as a dorsolateral pathway when processing salience per se, i.e. increased functional interactions between SNc, dorsolateral NAcc and dorsolateral and medial prefrontal cortex (PFC); and a ventromedial pathway during reward processing, i.e. increased functional coupling between VTA and ventromedial NAcc. Thus, these findings may not only accelerate the integration of animal models of brain function with human neuroscience but may also improve diagnosis and treatment in patients with neuropsychiatric disorders such as schizophrenia and depression in which dopaminergic dysfunction and aberrant attribution of salience have been implicated.
Gesehen am 30.07.2020